Integritas Badan Pemeriksa Keuangan Sebagai Supreme Audit Institution - Wisnhu Prabhawa; Eko Prasojo (Sospol : Jurnal Sosial Politik, 2021)
The Supreme Audit Agency (SAI) is a vital element in ensuring financial accountability in many countries. In Indonesia, BPK is the Supreme Audit Agency which has integrity in fighting corruption, maintaining transparency  and financial accountability, and strengthened democratic institutions. Unfortunately, the BPK faces a number of challenges in the issue of buying and selling opinions, tax audit limitations, and foreign debt, as well as limited institutional authority. This study applies a qualitative method that aims to evaluate the integrity of the BPK based on the dimensions of sound governance. Collecting data through literature studies and in-depth interviews. Data analysis through the stages of data reduction, data display and reference based on understanding the theoretical framework. It examines the integrity of BPK influenced by chellenges in quality and consistency of its actions. Dimensional processes still need to be optimized, such as the settlement of compensation by the treasurer, the use of SIPTL, the BPK Hearing Care Forum, and openness support from APIP. The dimensions of cognition and value have the similar challenges with ethical dimensions, namely integrity and transparency. The management and performance dimensions have challenges with the constitutional dimension of the word 'expected' which slightly hinders the fulfillment of the ideal quantity of quality human resources as BPK's backbone, a solution strategy to overcome the Minister of Finance's license, socialization and monitoring of BPK's opinion, as well as education on misperceptions regarding the assumption that WTP is clean from corruption and information technology. Financial Audit Examination with Financial Audit Examination.